Applied human resource management strategic issues and experiential exercises - York, Kenneth M.; Sage eBooks (Los Angeles, [Calif.] : SAGE, 2010)
York covers critical issues in the effective management of human resources, which can be used for class discussions, or be given as homework problems, or used as essay questions on tests.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Personnel management; Electronic books